Development of Digital-Based Teaching Materials (Flipbook) on Basic Passing Technique Material in Sepak Takraw Learning - Putu Bayu Sastrawan; I Ketut Semarayasa; Kadek Yogi Parta Lesmana (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
This research is motivated based on observations and interviews with students showing that 100% stated that there are no digital flipbook-based teaching materials in sepak takraw learning. Then 91.7% stated the need for learning innovations that support the learning process. This research aims to produce digital flipbook-based teaching materials on matari basic passing techniques in sepak takraw learning. This study uses the ADDIE model which consists of five stages, namely analysis, design, development, implementation, and evaluation. The data analysis techniques used include quantitative and qualitative descriptive analysis. The subjects in this study were four validators and students in the fifth semester of the Physical Education, Health, and Recreation (PE) study program who were selected using purposive sampling. Based on the expert test of the content of the material received a score of 100% very good, the learning design expert test got a score of 88% in the good category, the learning media expert test got a score of 97% very good, and the field practitioner expert test got a score of 98% very well and the individual trial got a score of 94% with the very good category, the small group trial got a score of 95% very good,  and large group trials with a score of 95% were excellent. Thus, this teaching material is very feasible to be used in the sepak takraw learning process in improving the quality of learning.